Kajian Terhadap Variasi Metode dan Bahan Pengawet pada Proses Pengawetan Bambu-Kayu di Indonesia (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Bamboo and wood are natural materials, each of which has a variety of uniqueness. Among its uniqueness is an irreplaceable building material between one another. However, weaknesses are also found in them especially related to termites or powder beetles. To be able to obtain maximum results in the use of these two materials, the preservation process was needed as a special treatment. With a variety of Bamboo preservation techniques, this paper tries to identify and examine various studies and best practices related to the Bambu-kayu preservation method in Indonesia. A qualitative approach was used with literature study techniques, field observations and in-depth interviews with entrepreneurs in preserving bamboo. From the results of the study obtained an illustration that the preservation method carried out depends on the needs of the user. It is also known that 10% Borak Boric concentrate has been able to be a chemical preservative that can be trusted to maximize material age. There should also be research on other preservatives, both chemical ones such as pyrolysis oil from plastic waste, as well as natural ones such as coconut shell liquid smoke and tobacco. Further research can also be focused on the strength of bamboo preserved by the preservation / boiling method. In addition to optimal material service age, it is necessary to consider several other criteria such as the ability to be mass produced / according to industry needs and able to be implemented significantly. Thus, it is expected that preservatives will be obtained that are safe for humans, environmentally friendly, workable and economical.